2010
DOI: 10.1177/1099636210388983
|View full text |Cite
|
Sign up to set email alerts
|

The quasi-static and blast response of steel lattice structures

Abstract: Lattice structures based on two simple architectures have been manufactured from 316L stainless steel using the selective laser melting process. The compressive properties of structures based on a body-centered cubic (BCC) and a similar structure with vertical pillars (BCC-Z) were initially investigated at quasi-static rates of strain. Blast tests were subsequently performed on the lattice structures as well as on lattice sandwich structures with CFRP skins. When subjected to quasi-static compression loading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 17 publications
4
39
0
4
Order By: Relevance
“…Similar observations regarding surface finish have been made by several authors who have utilised SLM [6][7][8]. From these investigations it can be concluded that a number of factors including laser power, movement speed and scanning direction all contribute to characteristics of the completed part.…”
Section: Bon Designsupporting
confidence: 79%
“…Similar observations regarding surface finish have been made by several authors who have utilised SLM [6][7][8]. From these investigations it can be concluded that a number of factors including laser power, movement speed and scanning direction all contribute to characteristics of the completed part.…”
Section: Bon Designsupporting
confidence: 79%
“…They observed a rate sensitivity of the yield strength of the lattice structures as well as an increase in the blast resistance of the lattice structures with increasing the yield strength. Smith et al [8] performed quasi-static and blast tests on additively manufactured lattice structures made of stainless steel 316L. They observed that there is significant increase in the lattice yield strength at high strain rates which improves the energy absorption of the lattices and makes them more capable of withstanding blast loads.…”
Section: Introductionmentioning
confidence: 99%
“…Little research so far was done on dynamic compression tests on lattice structures manufactured by SLM. Smith et al 21 have investigated the quasistatic and blast response of both BCCand BCC-Z type lattice structures. Their investigations show that the behavior of lattice structures is predictable and that the collapse mechanisms in blast response.…”
Section: State-of-the-artmentioning
confidence: 99%